Using smart ICT to provide weather and water information to smallholders in Africa: the case of the Gash River Basin, Sudan - Amarnath, Giriraj; Simons, G.W.H.; Alahacoon, Niranga; Smakhtin, Vladimir U.; Sharma, Bharat R.; Gismalla, Y.; Mohammed, Y.; Andriessen, M.C.M. (Elsevier, 2018)
In the Gash Delta of Eastern Sudan, spate irrigation (flood-recession farming) contributes substantially to rural livelihoods by providing better yields than rainfed dryland farming. However, spate irrigation farmers are challenged by the unpredictability of flooding. In recent decades, the number of farmers practicing spate irrigation has decreased, due to varying rainfall intensity and frequency, insufficient infrastructure and farmers’ limited capacity to manage such variations. One solution that may help farmers face such challenges is for them to access real-time water-related information by using smart Information and Communication a Technology (ICT). This paper shows how integrating remote sensing, Geographical Information Systems (GIS), flood-forecasting models and communication platforms can, in near real time, alert smallholder farmers and relevant government departments about incoming floods, using the Gash basin of Sudan as an example. The Ministry of Water Resources of Sudan used the findings of this study to transform farmers’ responses to flood arrival from being ‘reactive’, to planning for the flood event. Intensive on-site and institutional efforts to build the capacity of farmers, farmer organizations, development departments and officers of the Ministry helped to develop the initiative from simply sending ‘emergency alerts’ to enabling stakeholders to visually see the flood event unfolding in the region and to plan accordingly for storing water, operating spate-irrigation systems and undertaking cropping activities. The research, initially conducted on a 60 × 60 km site, was later extended to the entire Gash basin. The paper outlines how to develop tools that can monitor plot-specific information from satellite measurements, and supply detailed and specific information on crops, rather than providing very general statements on crop growth. Farmers are able to use such tools to optimize their farm profits by providing water to their crops in the right place, at the right time and in the right quantity. Finally, the work demonstrates the high potential of combining technology, namely remote sensing data and simple a agro-meteorological model with limited parameters, for large-scale monitoring of spate irrigation systems and information sharing to advise farmers as to how to apply this information to their managerial decisions.